Students’ Perceptions On The Use of Video Recording in Public Speaking Class: A Case Study in Perjuangan University Tasikmalaya - Dini Nurdiniati; Rina Ariyanti; Rita Rostiawati, (Journal of Applied Linguistics (ALTICS), 2024)
Video recordings are used in Public Speaking classes to deal with new situations and conditions of online learning during the spread of the Covid-19 disease. This research was conducted to determine students' perceptions of video recordings in public speaking classes. A descriptive qualitative approach was chosen as the research design. Data collection techniques using a questionnaire. This research involved 17 students from class 2020 and 2021 who had taken the Public Speaking course in the second semester at the University of Perjuangan. Student perceptions will be analyzed through three aspects, namely psychological aspects, academic aspects and technical aspects. The results of this study indicate that most students have a positive perception of the use of video recordings. Students acknowledge that video recording facilitates better speaking practice which in turn helps them improve their speaking skills and they feel that they can achieve learning competence (Academic aspect). The process of making video recordings was also assessed by students as fun and exciting (Psychological Aspect). Students also felt that there were no significant difficulties in the process of making the video (technical aspects). Based on these findings, video recordings are considered as a profitable and effective medium for students in Public Speaking courses. Keywords: Perception, Video Recording, Public Speaking Class.